THE MEASURING INDICATOR OF CHILD-FRIENDLY TEACHER IN EARLY CHILDHOOD EDUCATION INSTITUTION - Prima Suci Rohmadheny; Wahyu Nanda Eka Saputra; Raudia Utami; Dwi Isnawati (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2019)
This paper discussess the procedure and result of the formulation of the child-friendly teacher's skill in the Early Childhood Education Institution (PAUD). The formulation of the indicators was performed through the following steps: conducting conceptual study towards the child-friendly teachers’ skill in PAUD, constructing the operational definition from the child-friendly teachers’ skill, establishing operational definition, the operational definition was used to construct a blueprint containing indicators of child-friendly teachers in PAUD. The result of the present study is in the form of three indicators of child-friendly teacher. These indicators are teacher’s skill in planning, implementin, evaluating and reporting the result of the implementaion of non discriminative education stimulus, health, nutrition, care, and protection program for children in PAUD.